1975
DOI: 10.1002/ijc.2910150514
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human leukocyte migration in agarose by KCl extracts of carcinoma of the lung

Abstract: The leukocyte migration in agarose assay recently developed by Clausen (Clausen, 1971), was used to test 22 lung cancer patients against soluble extracts of allogeneic lung cancer and allogeneic normal lung. Seventeen were inhibited to a significantly greater degree by at least one tumor extract (average migration index (MI equals 0.58) than by the corresponding normal lung extract (average MI equals 0.83). DNCB-positive and DNCB-negative patients reacted with equal frequency to tumor extracts. Three patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

1975
1975
1980
1980

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Lymphocytes reacted most frequently with the targets cultured from lung tumours in cytotoxicity tests (Hellstrom et al, 1971;Baldwin et al, 1973;Vose et al, 1975;Pierce and De Vald, 1975) or with lung homogenates in leukocyte migration inhibition assays (Boddie et al, 1975;Vose et al, 1977a). Reactions in skin testing with tumour homogenates also showed organ-related reactivity (Hollinshead et al, 1974).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lymphocytes reacted most frequently with the targets cultured from lung tumours in cytotoxicity tests (Hellstrom et al, 1971;Baldwin et al, 1973;Vose et al, 1975;Pierce and De Vald, 1975) or with lung homogenates in leukocyte migration inhibition assays (Boddie et al, 1975;Vose et al, 1977a). Reactions in skin testing with tumour homogenates also showed organ-related reactivity (Hollinshead et al, 1974).…”
Section: Discussionmentioning
confidence: 98%
“…The implication of these studies is that tumours from the lung share common antigenic specificities not present on neoplasms arising at other sites. Reactivity against apparently non-malignant lung tissue in migration inhibition assays (Vose et at., 1975(Vose et at., , 1977aBoddie et al, 1975), the involvement of NK reactions and effector functions of non-T lymphocytes (Vose and Moore, 1977) against cultured allogeneic targets in cytotoxicity tests, may to some extent obscure this interpretation. However, the apparent autologous reactivity could arise from histocompatibility restriction of cytotoxicity to a common lung-tumour-associated antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Such data emphasizes that different modalities of membrane solubilization may yield different TAA. These data serve to suggest that lung TAMA-1 is not likely to have been present in biologically significant amounts in 3M KCI extracts tested by several researchers (Boddie et al, 1975;Dean et al, 1978;McCoy et al, 1977;Pierce & DeVald, 1975;Roth et al, 1975). However, other reports by Hollinshead et al (1974Hollinshead et al ( , 1975 are more likely to have contained lung TAMA-I.…”
Section: Discussionmentioning
confidence: 70%
“…Other investigators, using more crude lung TAMA generated by 3M KCI solubilization, have demonstrated cell-mediated immune (CMI) reactivity of lung-cancer patients to such preparations. The in vitro CMI methods have included lymphocyte blastogenesis Dean et al, 1978), leucocyte-migration inhibition (Boddie et al, 1975;Cannon et al, 1977;McCoy et al, 1977) as well as microcytotoxicity (Pierce & DeVald, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…RECENTLY, several investigators have reported that specific cellular anti-tumour reactivity can be detected by means of the leucocyte migration inhibition (LMI) test from capillary tubes (Cochran et al, 1973;Kjaer,1975;McCoy et al, 1975) and also by migration under agarose (Bergstrand et al, 1974;Boddie et al, 1975;Tautz et al, 1974). The purpose of the present study was to compare the macrophage electrophoretic mobility (MEM) test introduced by Caspary and Field (1970) with LMI under agarose (Clausen, 1971) using allogeneic KCI extracts of tumours and normal tissues, carcinoembryonic antigen (CEA) and human encephalitogenic protein (HEP).…”
mentioning
confidence: 99%